Prevalence and associated factors of Enterobius vermicularis infection in children from a poor urban community in Sri Lanka: a cross-sectional study - Suraweera, Osada S.A.; Galgamuwa, Lahiru S.; Iddawela, Devika; Wickramasinghe, Susiji (International Journal of Research in Medical Sciences, 2017)
Background: Enterobiasis (pin worm infection) is caused byEnterobius vermicularis(E. vermicularis). According to World Health Organization, over a billion people are infected worldwide. A cross-sectional study was carried out to determine the prevalence and factors associated withthe transmission ofE. vermicularis infection in children from a poor urban community in Sri Lanka. Methods:This study was conducted in the Hantana Tea Estate (HTE) in Kandy district of Sri Lanka. A cross-sectional study was conducted from September to December 2013. After obtaining informed consent, data (socio economic data, educational level, deworming history, conditions and availability of the sanitary and housing facilities) were collected using an interviewer administered questionnaire. Clean rectangular (2x3 cm) transparent adhesive cellulose tapes (scotch tape) were distributed among all participants to collect samples. Results: Out of the 204 children 65 (31.9%) were positive forE. vermiculariseggs.Children aged 1-3 years showed the highest prevalence rate (37.5%). The risk factors significantly associated withE. vermicularisinfection were, a lack of parental knowledge about pinworm infection (p<0.001), hand washing only with water before a meal (p< 0.001) and after defecation (p<0.029) and de-worming period more than three months (p<0.001). Age, sex, family clusters, sucking fingers, toilet facilities and socioeconomic status were not found to be significantly associated with the infection (p>0.05). Conclusion: This study showed a high prevalence of enterobiasis in children in Hantana Tea Estate indicating a high level of transmission. A lack of parental knowledge and poor personal hygiene were significantly associated with the transmission of E. vermicularis. Furthermore, the present study recommends mass medication of residents and their contacts to reduce the transmission of pin worm infection could be suggested. Further, it seems that singledose treatment may not be effective against enterobiasis. Therefore, treatment should be repeated 2 to 3 times at 3 weeks intervals.